Detection of Lotmaria passim, Crithidia mellificae and Replicative Forms of Deformed Wing Virus and Kashmir Bee Virus in the Small Hive Beetle (Aethina tumida) - Antonio Nanetti; James D. Ellis; Ilaria Cardaio; Giovanni Cilia (Pathogens, 2021)
Knowledge regarding the honey bee pathogens borne by invasive bee pests remains scarce. This investigation aimed to assess the presence in Aethina tumida (small hive beetle, SHB) adults of honey bee pathogens belonging to the following groups: (i) bacteria (Paenibacillus larvae and Melissococcus plutonius), (ii) trypanosomatids (Lotmaria passim and Crithidia mellificae), and (iii) viruses (black queen cell virus, Kashmir bee virus, deformed wing virus, slow paralysis virus, sacbrood virus, Israeli acute paralysis virus, acute bee paralysis virus, chronic bee paralysis virus). Specimens were collected from free-flying colonies in Gainesville (Florida, USA) in summer 2017. The results of the molecular analysis show the presence of L. passim, C. mellificae, and replicative forms of deformed wing virus (DWV) and Kashmir bee virus (KBV). Replicative forms of KBV have not previously been reported. These results support the hypothesis of pathogen spillover between managed honey bees and the SHB, and these dynamics require further investigation.